2018
DOI: 10.12669/pjms.342.12705
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anterior segment parameters after Nd: YAG laser Capsulotomy: Effect the design of intraocular lens Haptic

Abstract: Objective:To evaluate the changes in anterior segment parameters after neodymium–yttrium-aluminum-garnet (Nd:YAG) laser capsulotomy in 1-piece and 3-piece IOLs.Methods:In an institution, 65 eyes of 65 consecutive pseudophakic patients with posterior capsule opacification underwent Nd:YAG laser capsulotomy. The patients were divided into two groups according to the IOL type. Group-1 consisted of 35 subjects with 1-piece IOL and Group-2 consisted of 30 subjects with 3-piece IOL. Anterior segment parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Studies in the literature reported an increase of 15-30% in IOP despite prophylactic treatment (25)(26). However, Ozkurt et al reported no significant change in IOP after YAG PC (27). In this study, despite prophylactic treatment, IOP was measured between 40-46 mmHg in 2 cases in Group 1; it was brought under control at the end of the first month.…”
Section: Discussionmentioning
confidence: 50%
“…Studies in the literature reported an increase of 15-30% in IOP despite prophylactic treatment (25)(26). However, Ozkurt et al reported no significant change in IOP after YAG PC (27). In this study, despite prophylactic treatment, IOP was measured between 40-46 mmHg in 2 cases in Group 1; it was brought under control at the end of the first month.…”
Section: Discussionmentioning
confidence: 50%
“… 29 On the other hand, Akmaz et al found a significant myopic change in spherical error in the single- and three-piece lens groups and a significant myopic change in SE in the three-piece lens group. 27 …”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22] Three studies noted a hyperopic shift after the procedure, [23][24][25] while two observed a myopic change. 26,27 Many of these studies do not assess cylinder independently. Of the six that did, only two noticed a statistical change in cylinder at the latest follow-up visit, with both of those changes decreasing in magnitude, 26,28 supporting our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation